Force Entrepreneurship in Contemporary Russia - Вадим Викторович Волков (Journal of Economic Sociology, 2010)
In part 2 the author tries to put the organizations which are responsible forguaranteeingsecurity and have the opportunity to control the means of violence into the sphere of social-economic analysis. The theoretical approaches are mainly focused on actions of those who have access to the means of duress. Short theoretical description of force entrepreneurship is given after that. The third part discovers the first elementary form of force entrepreneurship – provision of protection services including so called “guarding racket”. Then the author analyzes the more complicated forms of force entrepreneurship – force partnership and force.